Corporate governance and technical efficiency of government linked companies (GLCs) in Malaysia: a stochastic frontier approach / Jennifer Tunga Janang - Tunga Janang, Jennifer (2017)
The performance of government linked companies (GLCs) has been the subject of scrutiny from both the perspective of academic research and policy formulation. With trade liberalization and increasing global market competition, GLCs efficiency becomes relevant to ensure sustainable economic growth not only for the Malaysian economy but to remain as key players in the regional and international markets. Corporate governance and how it has affected firm performance is a much-debated issue and there is voluminous literature aimed at understanding its role in maximizing firm profitability and market value. However, studies on its effects on the economic efficiency as another indicator for performance are still minimal. This study’s objectives are two folds: First, applying the Stochastic Frontier analysis with inefficiency effects model, in estimating technical efficiency of GLCs against selected foreign owned firms (FFs) as international benchmark. The analysis uses 31 GLCs and 15 FFs listed in Bursa Malaysia over a period between 2001 and 2012 (12 years). Second, applying a similar model to the 31 GLCs over the same period, and allowing inefficiency effects to be a function of a set of explanatory variables, that measures corporate governance mechanism. The results indicate that the GLCs estimated efficiency levels have improved over time. The levels tend to slowly converge with the FFs that represent international standard. The top GLCs are found to have been catching up faster, although they are still below the frontier of best practice. Labour input, as measured by staff costs and other personnel expenses, is found to have a strong and negative relationship with output generation, suggesting overcapacity in human capital. Thus, this study recommends GLCs should embark on capital intensive, human talent and productivity driven policy to ensure investment in labour input would not lead to further inefficiency. When incorporating corporate governance mechanism to examine GLCs technical inefficiency, and controlling for firm sector and size, the results show government ownership, board remuneration, change in directors, and the independence of the Board Audit Committee are significantly important in explaining technical efficiency. While ownership structure and directors’ incentive have been considered key corporate governance mechanisms to mitigate agency problem, this study finds that the effectiveness of the board is more relevant to address economic growth of the firm, thus supports the revised Malaysian Code of Corporate Governance, 2012 that propagate the importance of an effective Board of Directors.